Don’t forget to play! - Goh, Grace Hui Ern (2019)
‘We don’t stop playing because we grow old, we grow old because we stop playing.’ George Bernard Shaw. As children, we are encouraged to play. Parents and educators alike recognize play as a proponent of cognitive and social development and as a beneficial tool to spark creativity. Children do not need a reason to play, it comes naturally to them. This innate drive to play forms the bedrock of delightful memories we relish as children and reminisce as adults. As we age into adulthood, time becomes a precious commodity and the significance of play becomes easily dismissed as unimportant. Yet, play is so beneficial to our wellbeing it drives our creativity, aids in our problem solving capabilities and crucial to our emotional health. In our humdrum routines play serves to stimulate and in our busy workdays play provides a source of relaxation - how can we then view play as a waste of time? Inspired by the work of play researcher Dr Stuart Brown, this project explores the necessity of play and the repercussions of neglecting play in the lives of adults. By rethinking how play can be made accessible, this project hopes to reintroduce the value of play allowing adults to easily enter the state of rejuvenating play as children do.